Spectrum of mutations and phenotypic expression in patients with autosomal dominant hypercholesterolemia identified in Italy - Bertolini, Stefano; Pisciotta, Livia; Rabacchi, Claudio; Cefalù, Angelo B.; Noto, Davide; Fasano, Tommaso; Signori, Alessio; Fresa, Raffaele; Averna, Maurizio; Calandra, Sebastiano (Atherosclerosis, 2013)
To determine the spectrum of gene mutations and the genotype–phenotype correlations in patients with Autosomal Dominant Hypercholesterolemia (ADH) identified in Italy. The resequencing of LDLR, PCSK9 genes and a selected region of APOB gene were conducted in 1018 index subjects clinically heterozygous ADH and in 52 patients clinically homozygous ADH. The analysis was also extended to 1008 family members of mutation positive subjects. Mutations were detected in 832 individuals: 97.4% with LDLR mutations, 2.2% with APOB mutations and 0.36% with PCSK9 mutations. Among the patients with homozygous ADH, 51 were carriers of LDLR mutations and one was an LDLR/PCSK9 double heterozygote. We identified 237 LDLR mutations (45 not previously reported), 4 APOB and 3 PCSK9 mutations. The phenotypic characterization of 1769 LDLR mutation carriers (ADH-1) revealed that in both sexes independent predictors of the presence of tendon xanthomas were age, the quintiles of LDL cholesterol, the presence of coronary heart disease (CHD) and of receptor negative mutations. Independent predictors of CHD were male gender, age, the presence of arterial hypertension, smoking, tendon xanthomas, the scalar increase of LDL cholesterol and the scalar decrease of HDL cholesterol. We identified 13 LDLR mutation clusters, which allowed us to compare the phenotypic impact of different mutations. The LDL cholesterol raising potential of these mutations was found to vary over a wide range. This study confirms the genetic and allelic heterogeneity of ADH and underscores that the variability in phenotypic expression of ADH-1 is greatly affected by the type of LDLR mutation. ► LDLR, APOB and PCSK9 genes were analyzed in a large cohort of ADH patients. ► In the ADH heterozygotes the mutation detection rate in candidate genes was 82%. ► LDLR mutations were found in 97.4% of mutation positive ADH heterozygous patients. ► We found 237 LDLR mutations 45 of which had not been reported previously. ► LDLR mutation carriers had a more severe phenotype than APOB mutation carriers.